Effect of Ionic Liquids Additive on the Retention Factor of Different Kinds of Compounds - Heo, H.J.; Han, D.; Row, K.H. (Asian Journal of Chemistry, 2011)
Ionic liquids can be used as mobile phase additives in reversed-phase liquid chromatography (HPLC) when mixed with other solvents such as methanol and acetonitrile. The addition of ionic liquids can alter analytes' retention factors decrease band tailing, reduce band broadening and improve resolution partly because of the competition between imidazolium cations and the analyte's polar groups for the silanol group on the alkyl silica surface along with the formation of weak bilayer electronic structures on the C18 column. Five ionic liquids were used and their influences on the retention factors of different compounds were studied. Elution profiles were calculated by plate theory based on linear and quadratic equations of retention factor, ln k = ln kw + SC, ln k = L + MC + NC2, where C is the concentration of ionic liquid. The results show that all the five ionic liquids greatly affected basic compounds.